Preparation and Characterization of Montmorillonite Modified Chitosan Nano-composites for Zinc Metal Removal - Samsuri, Hairul Nazri (IRC, 2016)
Nano-composites adsorbent based on chitosan (CTS), the second largest abundant natural polymer in nature that contains high hydroxyl and amine groups has received significant interest in adsorption application especially on heavy metals. Raw montmorillonite (MMT) was purified and modified to form surfactant modified MMT (Na-MMT) by adding 1 M of sodium chloride (NaCl) to increase its electronegativity prior to the intercalation of 2:1 ratio of MMT and CTS through centrifugation and drying technique. MMT acts as the nano-filler while distilled water and 1 v/v % of acetic acid is used as the medium to disperse the MMT nanoparticles and CTS solution with pH adjusted to 5 throughout the intercalation process.